Comment on Kilian et al. Comparing Characteristics and Treatment of Brain Vascular Malformations in Children and Adults with HHT. J. Clin. Med. 2023, 12, 2704 - Eker, Omer F.; Dupuis-Girod, Sophie; Shovlin, Claire L.; Boccardi, Edoardo (Journal of clinical medicine, 2023)
We read with interest the recent article by Killian et al. regarding the characteristics and treatment of brain vascular malformations (VMs) in children and adults with hereditary hemorrhagic telangiectasia (HHT) [...]